Peran Kepuasan Pelanggan Dalam Memediasi Pengaruh Kualitas Layanan Dan Citra Merek Terhadap Loyalitas Pelanggan: Studi Pada Pelanggan GO-JEK Di Denpasar - I Putu Satya Nitya Ananda; Putu Yudi Setiawan (RELASI : JURNAL EKONOMI, 2024)
Online transportation is one form of the rapid development of technology. One company that has become a pioneer in providing online-based transportation services is PT. Indonesian Go-Jek. PT. Go-Jek Indonesia was pioneered by Nadiem Makarim in 2010 which at that time only served motorcycle taxi orders via telephone, but since January 2015, Go-Jek has launched a mobile application that can be used as a medium for ordering Go-Jek transportation online. Go-Jek itself is an intermediary that connects motorcycle taxi drivers with customers, where customers can monitor the position of motorcycle taxi drivers that have been ordered. This study aims to determine the role of customer satisfaction in mediating the effect of service quality and brand image on customer loyalty. The sample in this study amounted to 120. The sampling technique used was purposive sampling technique, namely the technique of determining the sample with certain criteria. This study used data collection techniques using the questionnaire method using the Google form. The data analysis technique in this study is the SEM analysis technique using the SmartPLS software analysis tool. The results of this study indicate that service quality has a positive and significant effect on customer satisfaction and loyalty. Brand image has no positive and significant effect on customer satisfaction and loyalty. Customer satisfaction has a positive and significant effect on customer loyalty. Customer satisfaction partially mediates service quality on customer loyalty. Customer satisfaction does not mediate brand image on customer loyalty. Go-Jek management is expected to continue to improve the quality of their services, especially in improving the discipline and skills of drivers, so that the company is able to provide maximum service.